Skin amyloid deposits and nerve fiber loss as markers of neuropathy onset and progression in hereditary transthyretin amyloidosis. (18th February 2022) - Leonardi, Luca; Adam, Clovis; Beaudonnet, Guillemette; Beauvais, Diane; Cauquil, Cécile; Not, Adeline; Morassi, Olivier; Benmalek, Anouar; Trassard, Olivier; Echaniz‐Laguna, Andoni; Adams, David; Labeyrie, Céline
Abstract: Background and purpose: This study was undertaken to assess skin biopsy as a marker of disease onset and severity in hereditary transthyretin amyloidosis with polyneuropathy (ATTRv‐PN), a treatable disease. Methods: In this single center retrospective study, skin Congo red staining and intraepidermal nerve fiber density (IENFD) were evaluated in symptomatic ATTRv‐PN patients and asymptomatic TTR gene mutation carriers between 2012 and 2019. Non‐ATTRv subjects with suspected small fiber neuropathy who underwent skin biopsy during the same timespan were used as controls. Results: One hundred eighty‐three symptomatic ATTRv‐PN patients, 36 asymptomatic carriers, and 537 non‐ATTRv patients were included. Skin biopsy demonstrated amyloid depositions in 80% of the 183 symptomatic cases. Skin amyloid deposits were found in 75% of early stage ATTRv‐PN patients, and in 14% of asymptomatic carriers. All 183 symptomatic and 34 of 36 asymptomatic patients displayed decreased ankle IENFD with a proximal–distal gradient distribution, and reduced IEFND correlated with disease severity and duration. Conclusions: Our study demonstrates skin amyloid deposits are a marker of ATTRv‐PN disease onset, and decreased IENFD a marker of disease progression. These results are of major importance for the early identification of ATTRv‐PN patients in need of disease‐modifying treatments. Abstract : Skin biopsy provides useful information in hereditary transthyretin amyloidosis with polyneuropathy. Amyloid deposition in skin is a biomarker of disease onset in paucisymptomatic subjects, especially in early onset Val30Met. Small nerve fiber reduction, which often precedes disease onset, correlates with disease severity.